Five-year standardised mortality ratios in a cohort of homeless people in Dublin. Issue 1 (25th January 2019) - Ivers, Jo-Hanna; Zgaga, Lina; O'Donoghue-Hynes, Bernie; Heary, Aisling; Gallwey, Brian; Barry, Joe
Abstract : Objective: To calculate standardised mortality ratios (SMRs) for a cohort of homeless people in the Dublin region over a 5-year period and to examine leading causes of death. Setting: Homeless services reporting deaths from homeless persons in their care across the Dublin Homeless Region. Methods: Death data among people who experience homelessness was acquired from the Dublin Region Homeless Executive (2011–2015) and validated from both death certificates and records from the Dublin Coroner's Office. Participants: Two hundred and nine deaths were recorded; of these 201 were verified (n=156 males, 77.6%). Deaths that could not be verified by certificate or coroners record were excluded from the study. Results: SMRs were 3–10 times higher in homeless men and 6–10 times higher in homeless women compared with the general population. Drug and alcohol-related deaths were the leading cause of death, accounting for 38.4% of deaths in homeless individuals. These were followed by circulatory (20%) and respiratory causes (13%). Conclusion: Mortality rates among homeless persons are exceptionally high. Services and programmes, particularly housing and those targeting overdose and alcoholism, are urgently needed to prevent premature mortality in this vulnerable population.